Muhammadiyah Education at Bringin Bendo Village During Covid-19 - Sifa’un Nazilah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
Coronavirus Disease 2019 (COVID-19) is known, originating from Wuhan, China. Found at the end of December 2019. This condition has an impact on Muhammadiyah education in the village of Bringin Bendo, Muhammadiyah is an organization that spreads the Islamic religion founded by KH Ahmad Dahlan, in this Muhammadiyah organization there is a structure of Muhammadiyah organizations that are arranged in stages, from the bottom, namely Branch, Branch, Region, Region and Center. Muhammadiyah education in this village has a big influence on the community, with the existence of Muhammadiyah education the community knows about this Muhammadiyah organization. But the existence of COVID-19 hampers the spread of the preaching of Muhammadiyah In Muhammadiyah education in des Abringin bendo there is formal education and non-formal education, besides that in Bringin Bend village there are also organizations that can support Muhammadiyah education such as asiyiyah and Nasyiatul Aisyiyah. This research is a qualitative descriptive research method. Observation, then concludes using the inductive-deductive method where this method raises the theoretical results and is connected with the results of the interview.